Effectiveness of Binahong (Anredera cordifolia) Leaf Extract in Suppressing The Growth of Xanthomonas oryzae and The Occurrence of Bacterial Leaf Blight Disease in Rice Plant (Oryza sativa) - Khotimah, Dwi Kusnul; Abadi, Abdul Latief; Choliq, Fery Abdul (University of Brawijaya, 2023)
Rice, as a staple food, is widely produced across Indonesia. However, bacterial leaf blight (BLB) in rice is caused by Xanthomonas oryzae pv. oryzae (Xoo) has been reported to cause significant crop yield losses. The continuous use of chemical bactericides to control BLB is not environmentally sustainable. This study investigated the potential of the Binahong plant as a botanical pesticide to suppress the growth of Xoo bacteria. Binahong is readily available in Indonesia and can be propagated generatively and vegetatively. The research employed a Completely Randomized Design (CRD) experimental method to evaluate the effectiveness of Binahong leaf extract against Xoo pathogens in vitro at various concentrations (0.5%, 1%, 1.5%, 2%) alongside positive and negative controls. In-vivo observations were made on several parameters: seed germination percentage, disease incidence, incubation period, and plant length. Data analysis revealed that Binahong leaf extract inhibited the growth of Xoo bacterial colonies in vitro at all tested concentrations (0.5% to 2%). Furthermore, soaking rice seeds in Binahong leaf extract was effective in vivo at all concentrations, demonstrating significant differences compared to the negative control and no significant differences compared to the positive control.